STRATEGY OF BROTOJOYO POST AGENT IN THE COMPETITION OF PACKAGE AND LETTER DELIVERY AGENTS: CASE STUDY POS AGENT BROTOJOYO SEMARANG - Heriawan , Bambang; Soelistiyono , Anitiyo (International Journal of Social and Management Studies, 2022)
The postal agent is a service unit managed by the other party (partners) that act for and on behalf of PT. Pos Indonesia (Persero) to conduct postal services in accordance with the prevailing agreement. The operation of the postal agent can be combined with the partner's services or other retailer businesses. Although the offer of this post agent Kemitraann has been a long time and much in demand by the community, but in fact the number of postal agents who are still a partner of PT Pos relatively little when compared to the number of package agents/courier from private companies. The problem is how the strategy used by postal agents Brotojoyo Semarang in the middle of the competition delivery agents and mail packages.The purpose of this research was made to determine the factors that have been held by the agent Brotojoyo post in the middle of competition. Research conducted at the post agent Brotojoyo Semarang Tengah subdistrict. The Peneltian design used Holistic single case study or a holistic single case study which is the research that puts a case as the focus of the research. This type of research is inferential. The data source in this research there are 2 kinds of data sources namely primary data and secondary data. The data collection methods used are methods of inquiry or questionnaire, interview method or interview, and observation method. Informant as the source of information is the principal, employee, and user of the postal agent Brotojoyo. In this research the data of the research results were analyzed by qualitative method by conducting direct observation or observation, interviews and documentation. The results obtained from the research we do is the location chosen by the post agent Brotojoyo indicates that the strategic location, where around the office of the post agent Brotojoyo there are many offices, schools and residents houses, so the strategy to get the customer in terms of location distance is very appropriate to be used for quality, from the information of the interview obtained that the quality provided in the form of delivery and pick-up of mail and packages that ontime, always careful Letters and packages received and carried, and assist in tracking. To service here all the parts related to the service that is in the agent Brotojoyo post is to always give a smile, friendly and put the customer first come first. Capital strategy used by the post agent Brotojoyo to back up financing of letters and packages are employees helping each other close the financing of the funds of the agent Pos employees first. In terms of the transaction, Pos agency delivers a fairly large cut to customers who send a large number of letters or packages. The last strategy is with follow-up strategy, so that the customer always loyal then always follow up to the customer, then after the beginning of the cooperation to make the MOU, always monitor the service in the pickup and delivery of mail and the package carried out by employees, so that the unwanted things can be reduced.